Perencanaan Fondasi Pada Pembangunan Gedung 5 Lantai Rumah Sakit Puri Asih Salatiga - Andini Eka Lestari; Rafly Nur Wahyuda; Totok Apriyanto; Agung Hari Wibowo (Jurnal Teknik Indonesia, 2024)
A foundation is a part of a system of substructures that holds its own weight and the entire force load of the superstructure, then passes it on to the soil and rock layers located underneath. Foundation Planning must be done carefully to obtain the appropriate carrying capacity to support the load of the structure on it. Good Foundation Planning will avoid the collapse of the structure on top of it. Before planning the foundation, it is good to carry out a soil investigation to determine the type of foundation used, in addition to the results of the soil investigation can determine the treatment of the soil so that the carrying capacity can support the construction to be built. In the research on foundation planning for this five-storey building structure, it is known that the carrying capacity value generated from sondir data with a qc value of 150 kg/cm2 calculated using the Mayerhoff method is 28198.26 kN/m2. With a combination of serving loads, the bore pile foundation is planned with a diameter of 0.5 meters and a depth of 4 meters. For reinforcement design, a combination of ultimate loads is used. From the results of the calculation of the main reinforcement used 12 D19 and the spiral reinforcement used Ø10.